Answer:
y = -x² + 6x - 1
General Formulas and Concepts:
<u>Algebra I</u>
- Standard Form: ax² + bx + c = 0
- Expanding by FOIL (First Inside Outside Last)
- Combining like terms
Step-by-step explanation:
<u>Step 1: Define equation</u>
y = -(x - 3)² + 8
<u>Step 2: Rewrite</u>
- Expand [FOIL]: y = -(x² - 6x + 9) + 8
- Distribute -1: y = -x² + 6x - 9 + 8
- Combine like terms: y = -x² + 6x - 1
Answer:
what are your choices
Step-by-step explanation:
Answer:
--- ---
| -5 -2 |
| 4 12 |
--- ----
Step-by-step explanation:
A matrix can only be added to (or subtracted from) another matrix if the two matrices have the same dimensions . To add two matrices, just add the corresponding entries, and place this sum in the corresponding position in the matrix which results.